Reproductive safety assessment of Thymus vulgaris L. extract and quantification of thymol sulfate in pregnant rats and fetuses using a validated LC/MS method of analysis - Zaineh Q. Tafesh, Kenza A. Mansoor, Nidal A. Qinna, Feras D. El-Hajji, Tawfiq A. Arafat, Luay F. Abu-Qatouseh, Bayan Y. Ghanim, Iman A. Basheti, Eyad M. Mallah (Journal of Applied Pharmaceutical Science, 2021)
The current study aimed to investigate the safety of ingesting standardized thyme extract (Thymus vulgaris L.) during pregnancy in rats. For this purpose, postmortem examination and thymol sulfate (TS) concentration in maternal and fetal effluent extracts were determined. TS concentrations were analyzed by developing and validating a new liquid chromatography–mass spectrophotometer method for quantification. Three dose levels of 1-, 10-, and 20-fold (x) of the recommended dose of standardized thyme extract in parallel to thymol were administered to evaluate the development of rat fetuses from the 5th to the 19th day of gestation. Blood samples from pregnant rats and fetal tissue samples were analyzed to detect the presence of TS that is a major thymol metabolite. The average concentration of TS detected in pregnant rats’ plasma-administered thyme extract was 648 ± 106 ng/ml at 1x dose compared to 3,429 ± 865 ng/ml for its equivalent amount of thymol compound. Quantities of TS in the dams and fetal tissue were found to increase in a dose-dependent manner. The administration of the 1x and 10x doses of the extract resulted in a significant increase in the fetal and placental weights. However, 20x dose of both thyme extract and thymol compound exhibited an increase in the number of adsorbing sites in the uterus and reduced birth weights compared to control. In conclusion, TS was capable of crossing the placental barrier in rats and increased the resorption index when high and repeated doses of thyme extract were administered. The current investigation highlights the expected danger of exceeding the therapeutic dose when consuming thyme remedies during pregnancy.
Keywords: Thyme, essential oil, toxicity, fetus, pregnancy, cough syrups.